Hierarchical coassembly of DNA–triptycene hybrid molecular building blocks and zinc protoporphyrin IX - Kumari, Rina; Singh, Sumit; Monisha, Mohan; Bhowmick, Sourav; Roy, Anindya; Das, Neeladri; Das, Prolay (Beilstein Journal of Nanotechnology, 2016)
Herein, we describe the successful construction of composite DNA nanostructures by the self-assembly of complementary symmetrical 2,6,14-triptycenetripropiolic acid (TPA)–DNA building blocks and zinc protoporphyrin IX (Zn PpIX). DNA–organic molecule scaffolds for the composite DNA nanostructure were constructed through covalent conjugation of TPA with 5′-C12-amine-terminated modified single strand DNA (ssDNA) and its complementary strand. The repeated covalent conjugation of TPA with DNA was confirmed by using denaturing polyacrylamide gel electrophoresis (PAGE), reverse-phase high-performance liquid chromatography (RP-HPLC) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). The biologically relevant photosensitizer Zn PpIX was used to direct the hybridization-mediated self-assembly of DNA–TPA molecular building blocks as well as a model guest molecule within the DNA–TPA supramolecular self-assembly. The formation of fiber-like composite DNA nanostructures was observed. Native PAGE, circular dichroism (CD) and atomic force microscopy (AFM) have been utilized for analyzing the formation of DNA nanofibers after the coassembly. Computational methods were applied to discern the theoretical dimension of the DNA–TPA molecular building block of the nanofibers. A notable change in photocatalytic efficiency of Zn PpIX was observed when it was inside the TPA–DNA scaffold. The significant increase in ROS generation by Zn PpIX when trapped in this biocompatible DNA–TPA hybrid nanofiber may be an effective tool to explore photodynamic therapy (PDT) applications as well as photocatalytic reactions.
Keywords: DNA nanostructure; DNA–organic hybrid; DNA self-assembly; 2,6,14-triptycenetripropiolic acid; zinc protoporphyrin IX